2013
DOI: 10.1021/ja4024868
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Homogeneous and Heterogeneous Water Oxidation Catalysis: Confirmation that [Co4(H2O)2(α-PW9O34)2]10– Is a Molecular Water Oxidation Catalyst

Abstract: Distinguishing between homogeneous and heterogeneous catalysis is not straightforward. In the case of the water oxidation catalyst (WOC) [Co4(H2O)2(PW9O34)2](10-) (Co4POM), initial reports of an efficient, molecular catalyst have been challenged by studies suggesting that formation of cobalt oxide (CoOx) or other byproducts are responsible for the catalytic activity. Thus, we describe a series of experiments for thorough examination of active species under catalytic conditions and apply them to Co4POM. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
218
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(228 citation statements)
references
References 97 publications
10
218
0
Order By: Relevance
“…An (Figure 22). [58,128] Recently,S oriano-Lópeze tal. reported aD FT study on the water oxidation mechanism catalyzed by this complex.…”
Section: àOoh]mentioning
confidence: 99%
“…An (Figure 22). [58,128] Recently,S oriano-Lópeze tal. reported aD FT study on the water oxidation mechanism catalyzed by this complex.…”
Section: àOoh]mentioning
confidence: 99%
“…[12][13][14][15][16] We recently demonstrated that three water-soluble Co-porphyrins, CoTPPS, CoTCPP, and CoTMPyP (Figure 1), are all highly active WOCs when using [Ru(bpy) 3 ] 2 + as a photosensitizer and Na 2 S 2 O 8 as a sacrificial electron acceptor; [17] Wang and Groves have also demonstrated that Co-porphyrins are also active as electrocatalysts for WO. [18] In the [Ru(bpy) 3 ] 2 + /Na 2 S 2 O 8 photoinitiated system some degradation of the sensitizer and catalyst cannot be avoided owing to the formation of highly oxidizing sulfate radical anions (SO 4 À C, E 1/2 > 3.15 V vs. NHE).…”
mentioning
confidence: 99%
“…Both cathodic adsorptive stripping voltammetry and inductively coupled plasma mass spectrometry measurements suggested that the possibly in situ generated Co(aq) 2+ species is not capable of catalyzing water oxidation, and the dominant WOC is still Co-POM [103].…”
Section: Cobalt-based Polyoxometalates (Co-pom)mentioning
confidence: 99%